Nurse-led interventions to promote hospitalized patients’ adherence to hand hygiene: narrative review - Nunes, Ana (2021)
Background: during the hospital admission, nurses play a fundamental role in the adherence to hand hygiene (HH) measures by patients and their families, enhancing the quality and safety of care. Objective: synthesize the latest scientific evidence regarding nurse-led interventions focused on hospitalized patients’ adherence to HH and its impact on preventing Healthcare-Associated Infections (HAIs). Methodology: following the PICOD mnemonic, a narrative review was conducted in MEDLINE (via PubMed), CINAHL (via EBSCO), and Cochrane Library. Two independent reviewers analyzed the relevance of the studies, extracted and synthesized data. Results: seven studies were included for review, published between 2016 and 2018. Three central themes emerged: i) nurse-led interventions that promote patients’ adherence to HH; ii) patients’ HH adherence and HAIs prevention; iii) the importance of person-centered nursing care in this scope. Conclusion: isolated interventions do not lead to adequate behavioural changes. Although educational interventions are the most common actions used by nurses, visual cues, distribution of informational material, provision of HH material, and creation of specific moments for HH are complementary strategies that enhance the efficiency and quality of the intervention.